The C‐type lectin receptor MGL senses N‐acetylgalactosamine on the unique Staphylococcus aureus ST395 wall teichoic acid. (8th July 2019) - Mnich, Malgorzata E.; van Dalen, Rob; Gerlach, David; Hendriks, Astrid; Xia, Guoqing; Peschel, Andreas; van Strijp, Jos A.G.; van Sorge, Nina M.
Abstract: Staphylococcus aureus is a common skin commensal but is also associated with various skin and soft tissue pathologies. Upon invasion, S . aureus is detected by resident innate immune cells through pattern‐recognition receptors (PRRs), although a comprehensive understanding of the specific molecular interactions is lacking. Recently, we demonstrated that the PRR langerin (CD207) on epidermal Langerhans cells senses the conserved β‐1, 4‐linked N ‐acetylglucosamine (GlcNAc) modification on S . aureus wall teichoic acid (WTA), thereby increasing skin inflammation. Interestingly, the S . aureus ST395 lineage as well as certain species of coagulase‐negative staphylococci (CoNS) produce a structurally different WTA molecule, consisting of poly‐glycerolphosphate with α‐O‐ N ‐acetylgalactosamine (GalNAc) residues, which are attached by the glycosyltransferase TagN. Here, we demonstrate that S . aureus ST395 strains interact with the human Macrophage galactose‐type lectin (MGL; CD301) receptor, which is expressed by dendritic cells and macrophages in the dermis. MGL bound S . aureus ST395 in a tagN ‐ and GalNAc‐dependent manner but did not interact with different tagN ‐positive CoNS species. However, heterologous expression of Staphylococcus lugdunensis tagN in S . aureus conferred phage infection and MGL binding, confirming the role of this CoNS enzyme as GalNAc‐transferase. Functionally, the detection of GalNAc on S . aureus ST395 WTA by human monocyte‐derived dendritic cells significantly enhanced cytokine production. Together, our findings highlight differential recognition of S . aureus glycoprofiles by specific human innate receptors, which may affect downstream adaptive immune responses and pathogen clearance.